2016
DOI: 10.1016/j.ijcha.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Femoral arterial closure using ProGlide® is more efficacious and cost-effective when ambulating early following cardiac catheterization

Abstract: ObjectiveThis was a prospective, single-center study evaluating the efficacy and cost-effectiveness of early ambulation (within 30 min) following femoral artery closure with the ProGlide® suture-mediated vascular closure device (PD) in patients undergoing diagnostic cardiac catheterization compared with manual compression.BackgroundIt is unclear whether early ambulation with ProGlide is safe or is associated with patient satisfaction and cost savings as compared with manual compression (MC).Methods and results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Although the literature still shows no consensus regarding this issue, studies have investigated shorter bed rest and have shown no harms to the patient. (21)(22)(23) Regarding nurse characteristics, most nurses were female, corroborating the characteristics of the profession overall. All participants had, at the minimum, specialization that contributed to obtaining scientific knowledge added to clinical experience.…”
Section: Discussionmentioning
confidence: 53%
“…Although the literature still shows no consensus regarding this issue, studies have investigated shorter bed rest and have shown no harms to the patient. (21)(22)(23) Regarding nurse characteristics, most nurses were female, corroborating the characteristics of the profession overall. All participants had, at the minimum, specialization that contributed to obtaining scientific knowledge added to clinical experience.…”
Section: Discussionmentioning
confidence: 53%
“…The safety of the PP device post diagnostic coronary catheterization has been established. 9 , 10 Use of multiple PPs in ‘preclose manner’ has been studied in femoral arteriotomies for TEVAR/EVAR/TAVR up to 24 F. 16 However, the safety of use of single PP device without heparin reversal has not been tested in CI which require relatively larger sheaths along with higher dose of anticoagulant and antiplatelet agents. In addition, it is not yet proven whether safety of SMVCD is a class effect or not.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported device failure rate of 3–7 percent. 9 , 10 , 12 , 19 , 20 , 21 , 22 An Indian study has reported a failure rate of 4% in 323 patients studied. 9 Device failure rates have reduced over time with evolving operator experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early ambulation has been shown to be cost-effective with the use of other vascular closure devices, such as the ProGlide® (Abbott Vascular, CA) suture-mediated device. 7 A study evaluating early ambulation (within 20 min following hemostasis) following the use of the StarClose® (Abbott Vascular, CA) vascular closure device has proven efficacy and safety. 8 Our study, albeit small, has shown that this approach for early ambulation is safe, with potential significant reduction in healthcare expenditure and human resource utilization.…”
Section: Discussionmentioning
confidence: 99%